Protoype Sistem Penyiram Lahan Perkebunan Kangkung Otomatis Berbasis Internet of Things dengan Logika Fuzzy Sugeno - Ismail Mahfuddin; Rakmat Kurniawan R; Aidil Halim Lubis (Journal of Computer System and Informatics (JoSYC), 2023)
Watering is one of the jobs that are routinely carried out in plant maintenance which usually causes various problems. One of them is the absence of the same measure of water quantity when watering will result in the plants being treated can experience excess or lack of water, causing the plants to dry out or rot and die. So we need a tool that can help in terms of watering plants. The internet of things-based automatic watering machine for water spinach plantations is expected to be a system to assist farmers in watering especially kale that can detect moisture in the soil and temperature around the land and has scheduling options, automatic fuzzy and manual that can be controlled via the android application. which has been designed and can work based on the selected option. This tool is made using the Sugeno fuzzy logic method because this method is suitable for use in making decisions to find the values ​​of humidity and temperature that fluctuate and are less certain. Based on the results of the study, the average percentage difference in the humidity sensor is 0.016 % and the accuracy (accuracy) on the humidity sensor circuit is 99.98%, while the percentage difference in the temperature sensor is 0.02% and the accuracy (accuracy) on the LM35 temperature sensor circuit is 99.99%.